2013
DOI: 10.1016/j.jsbmb.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of preneoplastic lesions by dietary vitamin D in a mouse model of colorectal carcinogenesis

Abstract: Highlights► High dietary vitamin D was able to prevent premalignant lesions caused by AOM/DSS. ► Increasing vitamin D intake raised serum 25-D3 levels reaching a plateau ≥1000 IU/kg. ► Serum 25-D3 levels over 30 ng/ml are needed to prevent tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…Several studies utilizing mouse models of colitis have shown that vitamin D can be beneficial in preventing or ameliorating inflammation and clinical disease (3032); however, these models do not typically progress to neoplasia. Recently, the DSS/AOM model, another model of inflammation associated cancer which does progress to dysplasia and tumor formation, was used to demonstrate that increasing concentrations of dietary vitamin D are protective against preneoplasic lesions in a dose-dependent manner (33). Consistent with these findings, we have shown that increased dietary vitamin D is effective at not only preventing inflammation and dysplasia, but subsequent invasive tumor formation as well.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies utilizing mouse models of colitis have shown that vitamin D can be beneficial in preventing or ameliorating inflammation and clinical disease (3032); however, these models do not typically progress to neoplasia. Recently, the DSS/AOM model, another model of inflammation associated cancer which does progress to dysplasia and tumor formation, was used to demonstrate that increasing concentrations of dietary vitamin D are protective against preneoplasic lesions in a dose-dependent manner (33). Consistent with these findings, we have shown that increased dietary vitamin D is effective at not only preventing inflammation and dysplasia, but subsequent invasive tumor formation as well.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the finding that the VDR controls nuclear β-catenin levels in colon cancer cells and can thus attenuate the effect of mutations that activate the Wnt/β-catenin pathway (12). Additionally, Hummel et al (13) showed that increasing dietary vitamin D intake prevents chemically induced preneoplastic lesions in mice colon. However, a large-scale randomized controlled trial, the Women's Health Initiative, found that calcium and vitamin D supplementation had no effect on the incidence of colorectal cancer compared with the placebo arm after a 7-year follow-up; this follow-up period is possibly insufficient for detecting the effect (14).…”
Section: Vitamin D Receptor Polymorphisms Are Associated With Reducedmentioning
confidence: 99%
“…How much vitamin D repletion is optimal? Studies in the AOM/DSS murine colon cancer model suggest that a dose-response relationship does exist; colonic dysplasia decreases as serum 25D3 levels increase from approximately 12 ng/mL to 60 ng/mL (43). The most striking effect was seen when mice with serum 25D3 levels of 12 ng/mL (100 IU/kg diet) were compared to those having a level of 30 ng/mL (400 IU/kg diet).…”
Section: Discussionmentioning
confidence: 99%